2016
DOI: 10.1021/acs.langmuir.6b02250
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Nitrogen-Doped Hollow Mesoporous Spherical Carbon Capsules for Supercapacitors

Abstract: A novel "dissolution-capture" method for the fabrication of nitrogen-doped hollow mesoporous spherical carbon capsules (N-HMSCCs) with high capability for supercapacitor is developed. The fabrication process is performed by depositing mesoporous silica on the surface of the polyacrylonitrile nanospheres, followed by a dissolution-capture process occurring in the polyacrylonitrile core and silica shell. The polyacrylonitrile core is dissolved by dimethylformamide treatment to form a hollow cavity. Then, the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…27 to 0 V. It can be seen that all the charge and discharge curves are highly symmetric, which further indicated that the electrode possessed an ideal capacitive performance. 22,38 It is also important to note that the specific capacitance of N-MCS reached 273 F g −1 at 0.5 A g −1 , which is much higher than that of many other types of nitrogen-doped carbon materials (Table 1) such as N-doped hollow carbon spheres/ sheets composites, 22 nitrogen-doping hierarchically porous carbon nanosheets, 44 nitrogen-doped hollow carbon spheres, 46 heteroatom-doped porous carbon, 47 nitrogendoped hollow mesoporous spherical carbon capsules, 48 porous nitrogen-doped hollow carbon spheres, 49 nitrogendoped macro-/mesoporous carbon foams, 50 nitrogen-doped graphene aerogels, 51 and porous nitrogen-doped carbon nanotubes. 52 In addition, the specific capacity of N-MCS was higher than that of carbon spheres (hexadecyl trimethylammonium chloride as the structure-directing agent) 34 and carbon sheets (ammonia as the catalyst) 22,37 reported in previous work, which is evidence that the excellent electrochemical performance may be ascribed to the unique composite structure and rich mesoporous structure.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…27 to 0 V. It can be seen that all the charge and discharge curves are highly symmetric, which further indicated that the electrode possessed an ideal capacitive performance. 22,38 It is also important to note that the specific capacitance of N-MCS reached 273 F g −1 at 0.5 A g −1 , which is much higher than that of many other types of nitrogen-doped carbon materials (Table 1) such as N-doped hollow carbon spheres/ sheets composites, 22 nitrogen-doping hierarchically porous carbon nanosheets, 44 nitrogen-doped hollow carbon spheres, 46 heteroatom-doped porous carbon, 47 nitrogendoped hollow mesoporous spherical carbon capsules, 48 porous nitrogen-doped hollow carbon spheres, 49 nitrogendoped macro-/mesoporous carbon foams, 50 nitrogen-doped graphene aerogels, 51 and porous nitrogen-doped carbon nanotubes. 52 In addition, the specific capacity of N-MCS was higher than that of carbon spheres (hexadecyl trimethylammonium chloride as the structure-directing agent) 34 and carbon sheets (ammonia as the catalyst) 22,37 reported in previous work, which is evidence that the excellent electrochemical performance may be ascribed to the unique composite structure and rich mesoporous structure.…”
Section: Resultsmentioning
confidence: 87%
“…Very little change in the specific capacitance was observed throughout the whole experiment, and 93% of the original capacitance was preserved after multiple cycles, which illustrated that the N-MCS electrode displayed good cycling and stability behavior compared to other N-doped carbon-based electrode materials (Table 2). 43,[47][48][49]51,56,58 In addition, the GCD curve of the 10,000th cycle showed no obvious difference from that of the first cycle (Figure 4(f)), 45 further indicating that the electrode possessed stable performance and good charge propagation. Two-electrode symmetric supercapacitors were fabricated to further investigate the capacitive performances of N-MCS as a real supercapacitor (Figure 5).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…There are also many studies on the synthesis of carbon spheres with poly(methyl methacrylate) (PMMA) spheres [40,120] and PAN spheres [133] as effective hard templates. For example, hollow carbonized PPy spheres were prepared by in situ chemical oxidative polymerization of pyrrole on the surfaces of PMMA spheres and subsequent pyrolysis.…”
Section: Hard Template Methodsmentioning
confidence: 99%
“…38 Chen et al have used polyacrylonitrile nanospheres as template to synthesis carbon nanoparticles. 39 Till date, there is no report available on the synthesis of spherical porous carbon hydrothermally by template free technique, to the best of our knowledge. In the present work, we have demonstrated a facile hydrothermal synthesis and followed by activation process for the preparation of porous spherical carbon nanostructures in situ doped with N and S from black mustard seed husk and investigated its applicability as a Li-ion battery anode and also, as a supercapacitor electrode.…”
Section: Introductionmentioning
confidence: 99%